Insulin-secreting non-islet cells are resistant to autoimmune destruction. - Lipes, M A (1996)
Transgenic nonobese diabetic mice were created in which insulin expression was targeted to proopiomelanocortin-expressing pituitary cells. Proopiomelanocortin-expressing intermediate lobe pituitary cells efficiently secrete fully processed, mature insulin via a regulated secretory pathway, similar to islet beta cells. However, in contrast to the insulin-producing islet beta cells, the insulin-producing intermediate lobe pituitaries are not targeted or destroyed by cells of the immune system. Transplantation of the transgenic intermediate lobe tissues into diabetic nonobese diabetic mice resulted in the restoration of near-normoglycemia and the reversal of diabetic symptoms. The absence of autoimmunity in intermediate lobe pituitary cells engineered to secrete bona fide insulin raises the potential of these cell types for beta-cell replacement therapy for the treatment of insulin-dependent diabetes mellitus.